Development And Validation Of Questionnaire To Assess Malaysian Parents’ Knowledge, Practice And Perception On Acetaminophen Poisoning In Children - Muhamad, Muhammad Zhariff (2019)
Introduction: Acetaminophen (paracetamol) poisoning may lead to serious complications and adverse health effects in children. A good knowledge, perception and practice is essential in ensuring the safe use of the drug among children. The objective of this study is to develop and validate a questionnaire to assess knowledge, perception and practice among Malaysian parents related to/ on acetaminophen poisoning in children. Methodology: A cross-sectional study was conducted among volunteered and consented Malaysian parents who attended Clinical Trial Centre, Advanced Medical and Dental Institute, Universiti Sains Malaysia and fulfilled the inclusion and exclusion criteria. A self-administered questionnaire was developed consisting of 67 items that takes 30 minutes to complete and well received by all respondents. The validation of the questionnaire involved content, face and construct validity stages. The evaluation included item-level content validity index (i-CVI) and face validity index (i-FVI) for content and face validity respectively. As for construct validity, the values of KMO and Bartlett’s sphericity test were taken into account for sampling adequacy as well as factor loading and communalities for the measurement of exploratory factor analysis. Reliability analysis involved the use of Cronbach’s alpha and corrected inter-item correlations (CITC). This questionnaire was divided into three domains, with 67 items distributed to respective domains. The development of questionnaire was aided from literature review and brainstorming session with parents.